Bank Lending Rate Behaviour in Nigeria: Exploring the Influence of Migrant Remittances - Nzeh, Innocent Chile; Ogwuru, Hycenth Richard Oguejiofoalu; Onwuemeka, Irene Olanma; Obiukwu, Ifeoma Sandralyn (Economics, Business, Accounting & Society Review, 2025)
The relevance of remittances as important source of inflows has led to an avalanche of studies directed at finding how the economy is impacted by such aspect of inflows. Despite having examined the impact of remittances on many macroeconomic variables, one particular area which has not been duly given attention in literature is the influence of remittances on the lending rate. In this paper, the focus is to evaluate the contribution of migrant remittances to the lending rate movement in Nigeria. The study employed the frameworks of auto regressive distributed lag (ARDL) bounds, Fully Modified Ordinary Least Squares (FMOLS) and Dynamic Ordinary Least Squares (DOLS) with annual dataset that covered the period from 1982 to 2022. The study finds that under the FMOLS and the DOLS, remittances impacted negatively on the lending rate but the outcome is not significant. However, under the ARDL the impact was negative and significant in the long-run while in the short-run it was positive and significant. The outcome of the control variables also shows that while exchange rate had a positive impact on the lending rate in all the models but none of the results is significant, the impact of both inflation rate and real interest rate is positive and significant in all the models. Interest rate spread is also found to be positive under the FMOLS and under the short-run ARDL.